2013
DOI: 10.1088/1367-2630/15/2/023038
|View full text |Cite
|
Sign up to set email alerts
|

Charge–spin–orbital states in the tri-layered nickelate La4Ni3O8: an ab initio study

Abstract: The electronic and magnetic structures of La 4 Ni 3 O 8 , an analogue of the hole doped cuprates, are studied using the configuration state constrained local-spin-density approximation plus Hubbard U calculations. It is found to be a C-type antiferromagnetic Mott insulator, in which an orbital hybridization strongly reduces an otherwise possible charge disproportionation. This state accounts for several experimental observations. The involved Ni 2+ high-spin state and its orbital configuration are found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…but this has been shown to be very unfavorable in energy 20 . If all the Ni ions have the same valence, the e g states, with 2.67 electrons per Ni on average can occur in two different ways: the LS state and the HS state that give rise to a metallic and an insulating state, respectively (Fig.…”
Section: +mentioning
confidence: 99%
“…but this has been shown to be very unfavorable in energy 20 . If all the Ni ions have the same valence, the e g states, with 2.67 electrons per Ni on average can occur in two different ways: the LS state and the HS state that give rise to a metallic and an insulating state, respectively (Fig.…”
Section: +mentioning
confidence: 99%
“…7 Moreover, the dimensionality-induced IMT occurs in bulk Ruddlesden-Popper series Sr n+1 Ir n O 3n+1 (n = 1, 2, and ∞). 8 The bulk T -type nickelates La n+1 Ni n O 2n+2 (n = 2, 3, and ∞) [9][10][11][12][13][14][15][16][17][18][19][20][21] with infinite NiO 2 square planes seem to be another candidate for the dimensionality-controlled IMT. They contain bilayer, trilayer and infinite-layer of NiO 2 planes for La 3 Ni 2 O 6 (n = 2), La 4 Ni 3 O 8 (n = 3) and LaNiO 2 (n = ∞), respectively, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Poltavets et al 10 and Liu et al 19 found a molecular correlated insulating ground state, which is similar to a partially charge-disproportioned insulating state proposed by Wu. 20 Anisimov et al 18 reported that LaNiO 2 is an AFM insulator similar to CaCuO 2 (Ref. 22), but it was suggested to be nonmagnetic (NM) and probably metal by Lee and Pickett.…”
Section: Introductionmentioning
confidence: 99%
“…In their pioneering work Kugel and Khomskii [2] have shown that when degenerate orbitals are partly filled, spin-orbital superexchange couples spin and orbital degrees of freedom. It leads to phases with spin-orbital superexchange in two-dimensional (2D) [3][4][5][6][7][8] or in three-dimensional (3D) [9][10][11][12][13][14][15][16][17][18][19][20] systems. When both spin and orbital degrees of freedom are active joint spin-orbital quantum fluctuations arise and may even destabilize long-range order [21].…”
Section: Introductionmentioning
confidence: 99%